Jamun (Syzygium cumini (L.) Skeels) seed bioactives and its biological activities: A review. (December 2022) - Kumar, Manoj; Hasan, Muzaffar; Lorenzo, Jose M.; Dhumal, Sangram; Nishad, Jyoti; Rais, Nadeem; Verma, Aman; Changan, Sushil; Barbhai, Mrunal Deepak; Radha; Chandran, Deepak; Pandiselvam, Ravi; et al.
Abstract: Jamun ( Syzygium cumini Skeels) is a nutritious fruit and has historically been used as both as an edible and a traditional medicine. The jamun seed is an inedible by-product of the fruit. However, their high concentration of phytochemicals makes them valuable components of nutraceuticals. Various studies on diverse biological activities of jamun seeds have warranted their application in human health and biomedical fields. This review paper discusses critically the phytochemical composition of jamun seeds and the bioactivities, including their antioxidant, anti-inflammatory, anti-cancer, antidiabetic, anti-microbial, anti-obesity, hepato-protective, cardio and gastro-protective properties. The bioactivity of jamun seed is related to the presence of phenols, flavonoids, steroids, alkaloids, triterpenoids, tannins, and saponins. Animal research in vivo, and in vitro experiments with human and animal cell models support the idea that jamun seed extract can be valuable additions in food and biomedical fields due to the diverse bio-functional properties. However, in-depth and systematic in vivo clinical trials using human subjects must be conducted to confirm the safe consumption limit and establish other therapeutic roles of jamun seeds for their abundant utilization as a nutraceutical or pharmacological component. Moreover, research is required to understand the exact mechanisms of the bioactivities exhibited by jamun seeds.